PTH, FGF-23, Klotho and Vitamin D as regulators of calcium and phosphorus: Genetics, epigenetics and beyond - Portales-Castillo, Ignacio; Simic, Petra (Frontiers in Endocrinology, 2022)
The actions of several bone-mineral ion regulators, namely PTH, FGF23, Klotho and 1,25(OH)2 vitamin D (1,25(OH)2D), control calcium and phosphate metabolism, and each of these molecules has additional biological effects related to cell signaling, metabolism and ultimately survival. Therefore, these factors are tightly regulated at various levels – genetic, epigenetic, protein secretion and cleavage. We review the main determinants of mineral homeostasis including well-established genetic and post-translational regulators and bring attention to the epigenetic mechanisms that affect the function of PTH, FGF23/Klotho and 1,25(OH)2D. Clinically relevant epigenetic mechanisms include methylation of cytosine at CpG-rich islands, histone deacetylation and micro-RNA interference. For example, sporadic pseudohypoparathyroidism type 1B (PHP1B), a disease characterized by resistance to PTH actions due to blunted intracellular cAMP signaling at the PTH/PTHrP receptor, is associated with abnormal methylation at the GNAS locus, thereby leading to reduced expression of the stimulatory G protein α-subunit (Gsα). Post-translational regulation is critical for the function of FGF-23 and such modifications include glycosylation and phosphorylation, which regulate the cleavage of FGF-23 and hence the proportion of available FGF-23 that is biologically active. While there is extensive data on how 1,25(OH)2D and the vitamin D receptor (VDR) regulate other genes, much more needs to be learned about their regulation. Reduced VDR expression or VDR mutations are the cause of rickets and are thought to contribute to different disorders. Epigenetic changes, such as increased methylation of the VDR resulting in decreased expression are associated with several cancers and infections. Genetic and epigenetic determinants play crucial roles in the function of mineral factors and their disorders lead to different diseases related to bone and beyond.